Association of co-exposure to heavy metals with renal function in a hypertensive population. (March 2018) - Wu, Weixiang; Zhang, Ke; Jiang, Shunli; Liu, Dayang; Zhou, Hao; Zhong, Rong; Zeng, Qiang; Cheng, Liming; Miao, Xiaoping; Tong, Yeqing; Lu, Qing
Abstract: Background: Chronic kidney disease (CKD) is an increasing health problem worldwide. Recent studies have suggested the potential associations between exposure to metals and CKD events, particularly in participants with hypertension. However, relevant studies are limited. Objectives: We aimed to explore the associations of metal exposure with renal function in participants with essential hypertension. Methods: Nine hundred and thirty-four participants with essential hypertension were recruited at the Department of Cardiology, Union Hospital, Wuhan, China. We measured the levels of chromium, cadmium, thallium and uranium in urine and calculated the estimated glomerular filtration rate (eGFR) for renal function. Multivariable linear regression models adjusted for potential confounders were applied. Results: After adjusting for potential confounders and other metals, doubling of urinary chromium or uranium levels decreased eGFR by 2.90 (95% confidence interval, 2.04 to 3.76) and 1.87 (0.58 to 3.15) mL/min per 1.73 m 2, respectively. Co-exposure to chromium and uranium was found to greatly decrease eGFR, particularly in women. Compared with those in the low exposure group, women with high exposure to chromium and uranium had a 11.36 (3.66 to 19.07) mL/min per 1.73 m 2 adjusted decline in eGFR. Higher urinary thallium levels were positively related to elevated eGFR in men. The adjusted increase in eGFR with doubling of thallium levels was 3.12 (1.14 to 5.10) mL/min per 1.73 m 2 . Sex-difference in the associations of exposure to heavy metals with eGFR was also suggested. Conclusions: Our findings suggest that environmental exposure to chromium and uranium might contribute to a decline in eGFR in individuals with hypertension. The associations of exposure to heavy metals with eGFR might be sex-different. Further studies are warranted to confirm our findings and clarify the underlying mechanisms. Highlights: Renal effects of multiple metals were first assessed in a hypertensive population. Exposure to chromium or uranium might decrease eGFR in hypertensive participants. Combined effect of chromium and uranium on renal function was suggested. Urinary thallium was positively associated with eGFR in men participants. Sex-difference in the associations of heavy metals with eGFR was suggested.